Screening of important autoinduction medium composition for high biaomass production of E. coli expressing recombinant bromelain - Jamaluddin, Mohd Jamil Aizat; Amid, Azura; Azmi, Azlin Suhaida; Othman, Muhd. Ezza Faiez (Journal of Pure and Applied Microbiology, 2014)
Bromelain, a naturally available therapeutic protease enzyme from pineapple stem, was expressed in Escherichia coli using autoinduction-based fermentation medium. There are numerous recombinant proteins functionally expressed in E. coli using this autoinduction approach. Preliminary media trials have shown that this medium is capable of producing a high cell density batch culture as claimed. Since the level of soluble expression is both protein and host/strain specific, further screening to identify significant media components affecting biomass production is therefore required. Currently, screening of full autoinduction medium components has yet to be examined elsewhere in the literature due to its tedious nature. Hence, the application of a fractional factorial design for identifying significant components in the autoinduction formulation was reported. Statistical analysis showed that glucose, glycerol and L-arabinose were most significant components influencing the biomass production. However, their effects were demoting rather than promoting the biomass production at elevated concentrations in shake flask culture. The highest biomass production (7.3 g/l) was achieved at low levels (-1). This represents 0.05 % (w/v) glucose, 0.5 % (w/v) glycerol, without the need of additional L-arabinose inducer. For a low number of experimental runs, this statistical approach has been proven efficient for screening vital medium components in comparison to conventional method.